Determinantes do custo de comércio bilateral - Honorio Kume (Instituto de Pesquisa Econômica Aplicada (IPEA), 2021)
– High trade costs make it difficult to fully exploit comparative advantages and reduce the level of income. This paper estimates the cost of trade and its main determinants in the period 1995-2015 using information on domestic sales and exports by destination country of the input matrix product between OECD countries. The results indicate in this period the median cost of bilateral trade fell 8.7% in high-income countries, 14.9% in middle-income countries and 15.5% in low-income countries, and the drop was more pronounced in the period 1995-2005 than in the period 2005-2015. The tariff policy - unilateral or by trade agreements - and the management of the logistics chain are the instruments that cause the greatest impacts on trade costs.
Keywords: F13; 330; trade cost; tariff; logistic chain